Process validation of pregelatinized arrowroot starch - Bravo, Israel S.; Bautista, Jocelyn S. (Manila College of Pharmacy, University of the Philippines, 1996)
This study involves the process validation of pregelatinized arrowroot starch. The study aims to confirm the documented procedure and the conditions specified in order to produce the modified starch. Arrowroot starch, obtained from Bataan and Laguna, was modified by heating a 42% aqueous suspension. The resulting gelatinized starch was then subjected to tests required by the USP/NF for compliance with the specifications set and identity as well as purity were established. Powder characteristics were also determined. The starch was able to conform with the ID test, pH, Oxidizing Substances, Sulfur Dioxide Content and Residue on Ignition. The tests for Loss on Drying, Moisture Determination and Bulk Density yielded results which did not conform with those specified by the pharmacopeia. The process by which pregelatinized arrowroot starch is made was feasible but minor modifications were employed to reduce the difficulty encountered.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1996.
Keywords: Arrowroot powder; Starch; Araru